Evolução histórica dos processos de transformação curricular do ensino técnico em Santa Fe (1984-2005) - Ludueña, Cecilia (Universidad Nacional del Litoral, 2020)
This article discusses some historical approximations to the development of the curricular transformation processes undergone by technical educationin Santa Fe province. An introduction is provided todescribe the curricular construction processes in technical education throughout history, delving deeply intoa more delimited period from 1984 to 2005 approximately. The analysis and description of these processes are framed into the documents and laws thataccount for current regulations on technical education.